2022
DOI: 10.1001/jamanetworkopen.2021.44170
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of a Clinical Score for Patients With Neuroendocrine Tumors Under Consideration for Peptide Receptor Radionuclide Therapy

Abstract: IMPORTANCE Despite the benefit of peptide receptor radionuclide therapy (PRRT) for patients with well-differentiated neuroendocrine tumors (WD NETs), no clinical metric to anticipate benefit from the therapy for individual patients has been previously defined. OBJECTIVETo assess whether the prognostic ability of the clinical score (CS) could be validated in an external cohort of patients with WD NETs. DESIGN, SETTING, AND PARTICIPANTS This multicenter cohort study's analysis included patients with WD NETs who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…A review of patients from another tertiary center showed a progression-free survival of 21.6 months for the study group and 13.3 months for patients with pancreatic primary tumors [ 3 ]. A multi-center review of patients treated with 177 Lu-dotatate showed an objective response rate (18.7%) that was nearly identical to our findings [ 12 ]. We therefore confirm the reproducibility of these findings, which will be useful data to help design future prospective studies in pretreated populations.…”
Section: Discussionsupporting
confidence: 88%
“…A review of patients from another tertiary center showed a progression-free survival of 21.6 months for the study group and 13.3 months for patients with pancreatic primary tumors [ 3 ]. A multi-center review of patients treated with 177 Lu-dotatate showed an objective response rate (18.7%) that was nearly identical to our findings [ 12 ]. We therefore confirm the reproducibility of these findings, which will be useful data to help design future prospective studies in pretreated populations.…”
Section: Discussionsupporting
confidence: 88%
“… 38 In addition, recent retrospective studies have suggested that upfront PRRT after progression under SSA significantly improved PFS compared with upfront chemotherapy or targeted therapy in all NET, positioning PRRT earlier in the therapeutic sequence. 51 , 52 Other ongoing RCT such as Compete (NCT03049189) or Compose (NCT04919226), comparing PRRT with everolimus or chemotherapy, should help confirm these data.…”
Section: The Sequence Optionsmentioning
confidence: 99%
“… 52 Recent studies have also suggested that earlier incorporation of PRRT post-SSA may increase the anti-tumor benefit from the therapy patients derive. 56 The addition of everolimus to SSA therapy improves biochemical response among 61% of patients, incrementally better than the biochemical response rate of 54% among patients receiving SSA monotherapy. 53 The various liver embolization therapies generally achieve symptom reduction and biochemical response in 82% and 63% of patients, respectively.…”
Section: Gaps In Management Optionsmentioning
confidence: 99%